OC-029 Non-invasive screening for colorectal adenomas using plasma micrornas. (22nd June 2015) - Verma, AM; Patel, M; Aslam, MI; Wurm, P; Jameson, J; Pringle, JH; Singh, B
Abstract : Introduction: In the UK BSCP, patients aged 60–75 are screened using biennial faecal occult blood testing (FOBt), FOBt+ patients undergo colonoscopy. At screening colonoscopy, yield for adenomas is 46.5%, adenocarcinomas in 6%. 1 Whilst effective, FOBt lacks high sensitivity, specificity and accuracy – half of screening colonoscopies are normal or reveal haemorrhoids/diverticular disease (DD). 1 One off sigmoidoscopy screening ("bowel scope") is being introduced for patients aged 55 after a large trial showed 23% reduction in CRC incidence. 2 However, endoscopy based screening is invasive, resource intensive and can cause harm. Uptake of FOBt screening is <60%. 1 Early reports suggest this is lower for bowel scope. A blood based biomarker screening test is appealing. Method: We investigated microRNAs (miRs) – short non-coding RNA molecules as potential biomarkers. 181 FOBt+ patients undergoing BCSP colonoscopy and 29 patients undergoing planned polypectomy were recruited (blood samples taken pre-procedure). 210 patients – 128 male, 82 female. 117 with adenomas, 12 with CRC, 81 controls (normal or non-adenoma/adenocarcinoma). RNA was extracted from plasma and processed. Pooled groups of patients with adenomas and controls were analysed using array cards. MiRs 19a, 98, 146b, 186, 331–5p, 452 and 625 were identified as candidate biomarkers. Cases were analysed for candidate miRs using quantative polymerase chain reaction. Results: Candidate miRs showed significant levels of expression in patients with adenomas compared to controls. MiRs 19a, 331–5p, 452 p = < 0.05, miRs 98, 146b p = < 0.01, miRs 186, 625 p = < 0.001. Modelling of miR panels were performed, ROC curve analysis showed: Polyps (excl hyperplastic) in males, panel; miRs 98, 186, 452, sensitivity 0.600/specificity 0.872. Adenomas in males, panel; miRs 98, 186, 452, sens 0.606/spec 0.875 or sens 0.591/spec 0.900. Polyps (excl hyperplastic) in pts with DD/haemorrhoids, panel; miRs 186, 452, 331–5p, sens 0.600/spec 0.889 or sens 0.633/spec 0.867. Adenomas in pts with DD/haemorrhoids, panel; miRs 625, 452, 331–5p, sens 0.714/spec 0.864. Conclusion: This study suggest plasma microRNAs are potential screening biomarkers for male patients with colorectal polyps/adenomas and patients with adenomas and background DD/ haemorrhoids. Further study is needed to validate these exciting findings. Disclosure of interest: None Declared. References: Lee TJW, Rutter MD, Blanks RG, et al . Colonoscopy quality measures: experience from the NHS Bowel Cancer Screening Programme. Gut 2012;61:1050–1057 Atkin WS, Edwards R, Kralk-Hans I, et al . Once-only flexible sigmoidoscopy screening in prevention of colorectal cancer: a multicentre randomised controlled trial. Lancet 2010;375:1624–1633